2008
DOI: 10.1111/j.1467-8624.2007.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Trajectories of Bullying and Associated Factors

Abstract: Trajectories in bullying through adolescence were studied along with individual, family, and peer relationship factors. At the outset, participants' ages ranged from 10 to 14; 74% identified as European Canadian with the remainder from diverse backgrounds. With 8 waves of data over 7 years, 871 students (466 girls and 405 boys) were studied to reveal 4 trajectories: 9.9% reported consistently high levels of bullying, 13.4% reported early moderate levels desisting to almost no bullying at the end of high school… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
250
3
29

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 355 publications
(311 citation statements)
references
References 57 publications
29
250
3
29
Order By: Relevance
“…This finding is consistent with research on the development of bullying Pepler et al, , 2008). It appears that many children and youth who victimize peers eventually desist during adolescence, perhaps due to increased levels of empathy and decreased tolerance for people who are hurtful and mean (Galambos et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with research on the development of bullying Pepler et al, , 2008). It appears that many children and youth who victimize peers eventually desist during adolescence, perhaps due to increased levels of empathy and decreased tolerance for people who are hurtful and mean (Galambos et al, 2003).…”
Section: Discussionsupporting
confidence: 92%
“…Our results did show that boys reported more bullying than girls. However, this gender difference in the reporting of bullying behaviour is a consistent feature of the bullying literature, even in those studies using more comprehensive self-reported bullying questionnaire measures (e.g., Pepler Jiang, Craig, & Connolly, 2008;Crick & Grotpeter, 1995), as well as single item bullying measures (e.g., Nansel et al, 2001), and peer-rated bullying nomination measures (e.g., Boulton & Smith, 1994). The fact that the current study also found this consistent gender difference using a highly abbreviated measure of bullying using only two categories of response (never vs. sometimes/always) lends support to the accuracy of both the single item and the response options.…”
Section: Limitationsmentioning
confidence: 94%
“…Bullying is a sub-type of aggression aimed primarily at harming the relationship between peers (Marini et al, 2006;Pepler, Jiang, Craig, & Connolly, 2008) and, while a comprehensive examination of the vast bullying literature is outside the scope of the present paper, a number of central issues will be used to inform our understanding of incivility, including: 1) the predominant focus on the physical aspects of bullying; 2) the lack of understanding of the heterogenous nature of bullying; 3) the serious underestimation of the pervasiveness and impact of indirect types of bullying; 4) the short and long-term consequences Figure 2 Multidimensional Bullying Identification Model The Thin Line Between Civility and Incivility of this type of meanness; and 5) most importantly, the failure to appreciate the transformation of bullying to fit in different settings such as the world of academia. A particularly valuable distinction borrowed from the bullying literature (Marini et al, 2006;Marini, Dane, & Kennedy, in press), which focuses on the forms, functions and types of involvement, is illustrated in Figure 2.…”
Section: Aspects Of Bullying That Can Contribute To the Understandingmentioning
confidence: 99%